Pengaruh Promosi Dan Citra Merek Terhadap Keputusan Pembelian Minuman Siap Saji Merek Pokka Pada PT Esham Dima Mandiri - Sasta Caroline Silalahi; Ansari Grace Simalongo K. kintdy (Universitas Gorontalo, 2019)
Nowadays business competition is getting sharper, both domestic and global markets. Consumers become more thorough in making purchases and determining the brand of a product they want. With this situation, it encourages companies to be able to attract consumers, offer products that are quality and pay attention to the brand accompanied by attractive promotions. This competition can be overcome if consumers can feel loyal to a particular brand. The way the company influences consumers is through promotion and brand image. By maximizing both of these methods, it is expected to increase customer purchasing decisions. This study aims to determine the effect of simultaneous and partial of the promotion variables and brand image on the decision to purchase the ready-to-drink beverage brand Pokka. The sample used was 125 respondents from a population of 182 customers. The results have a significant effect on customer purchasing decisions.